Introduction - (:unkn) unknown (Springer Netherlands, 2007)
Crimean-Congo hemorrhagic fever (CCHF) is a fatal viral infection described from parts of Africa, Asia, Eastern Europe, and the Middle East [15, 20, 50, 52]. The CCHF virus (CCHFV) belongs to the genus Nairovirus in the family Bunyaviridae and causes a severe disease in humans, with a reported mortality rate of 3-30% [15]. The geographic range of CCHFV is the most extensive of the medically significant tick-borne viruses. Humans become infected through the bites of ticks, by contact with a patient with CCHF during the acute phase of infection, or by contact with blood or tissues from viremic livestock [52]. © 2007 Springer Netherlands. All rights reserved.